Presence of susceptible wild strains of Anopheles gambiae in a large industrial palm farm located in Aboisso, South-Eastern of Côte d’Ivoire - Sadia-Kacou, Cécile M. A. (Malar J, 2017)
BACKGROUND: The effectiveness of malaria control programmes through implementation of vector control activities is challenged by the emergence of insecticide resistance. In the South-Eastern region of Côte d’Ivoire, where palm oil plantations remain the predominant agricultural crop, the susceptibility of wild Anopheles gambiae sensu lato species is still unknown and thus requires a particular attention. The current study was carried out to address the gap by in-depth characterization of susceptibility level of An. gambiae mosquitoes from Ehania-V1 to WHO-recommended doses of six insecticides belonging to available classes and also to screen a subset for target site mutations and possible inhibition of P450 enzymes. RESULTS: Overall results showed variable resistance profile across WHO-recommended insecticides tested. Mortalities ranged from 8.3% (the lowest mortality was recorded with DDT) to 98% (the highest mortality was recorded with fenitrothion). Importantly, mortality to deltamethrin, an important pyrethroid used in public health for impregnation of mosquito nets was close to 98%, precluding a possible susceptibility to this insecticide, albeit further investigations are required. Pre-exposure of An. gambiae s.l. to PBO did not show any significant variation across insecticides (p = 0.002), although a partial increase was detected for alphacypermethrin and bendiocarb, suggesting a low of activity of cytochrome P450 enzymes (p = 0.277). High frequency of kdr L1014F was recorded in both Anopheles coluzzii (91%) and in An. gambiae (96%), associated with ace-1 (R) G119S mutation at low frequency (<20%). CONCLUSION: The high mortality rate to deltamethrin, organophosphate and the non-detection of P450 activity in resistance observed in Ehania-V1 appears as a positive outcome for further control strategies as metabolic-based P450 resistance remains major challenge to manage. These results should help the National Malaria Control Programme when designing strategies for vector control in palm oil areas of Côte d’Ivoire. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-017-1804-1) contains supplementary material, which is available to authorized users.